Coherent wireless optical communications with predetection and postdetection EGC over Gamma-Gamma atmospheric turbulence channels - Niu, Mingbo; Schlenker, Josh; Cheng, Julian; Holzman, Jonathan F.; Schober, Robert (Journal of Optical Communications and Networking, 2011)
Wireless optical communication systems with coherent detection are analyzed for GammaGamma distributed turbulence channels. In addition to the shot noise, we consider the impacts of both turbulence amplitude fluctuations and phase fluctuations on the error performance. Error rate analyses of predetection and postdetection equal gain combining (EGC) are carried out. We derive the exact error rate expressions for predetection and postdetection EGC using a characteristic function method. In the case of predetection EGC, we also study the impact of phase noise compensation error on the error rate performance. It is shown that the error rate performance of predetection EGC is sensitive to phase noise compensation errors for both weak and strong turbulence conditions. In order to alleviate the impact of phase noise, postdetection EGC with differential phase-shift keying is introduced and analyzed. In addition, postdetection EGC is compared with predetection EGC in the presence of phase noise compensation errors, and it is found to be an effective alternative to predetection EGC with low complexity implementation. © 2009 OSA.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Atmospheric turbulence; Coherent detection; Diversity; Optical communications; Phase noise